Rapid and Sensitive E-Coli DNA Detection by Titanium Dioxide Nanoparticles - K. F., Chong; Sh., Nadhirah; N., Zainudin; M. N. B., Derman; Ruslinda, A. Rahim (2014)
Escherichia Coli (E. coli) issue has been discovered since 1985 according to its ability to cause large outbreaks of gastrointestinal illness especially O157:H7 type. A new and simple method for label free, rapid and inexpensive of titanium dioxide (TiO2) nanoparticles biosensor based transducer on E. Coli DNA has been fabricated via sol-gel spin-coating technique. A simple quantitative approach was used to detect the existence of E. coli on the fabricated device. Extremely small steady current (picoammeters) were achieved, which indicates that this device can possibly go to very high sensitivities sensor towards DNA detection. A simple electrical signal of current-to-voltage (I-V) which provides small current was used to verify all the measurement of the device. (3-Aminopropyl)triethoxysilane (APTES) was functionalized through silanization process to modify the surface of TiO2 nanoparticles through the covalent bond between hydroxyl groups of TiO2 and organofunctional alkoxysilane group from APTES. The probe DNA was successfully immobilized and performed for hybridization with complementary DNA when the current is 3.5 E-10 ≤ I ≤ 4.5 E-10 A. The microchip showed reliable capture of E. coli in deionized water with an efficiency of 33.6% ± 5% at concentration of 1.0 μM.